Pd-Catalyzed Homologation of Arylboronic Acids as a Platform for the Diversity-Oriented Synthesis of Benzylic C–X Bonds - Bastick, Kane A. C.; Watson, Allan J. B. (Synlett, 2023)
We report a synthetic platform for the formation of benzylic C–X bonds. Benzylboronic acid pinacol (Bpin) esters are useful synthetic intermediates but are commercially uncommon, leading to preparations that typically rely upon stoichiometric metalation. Pd-catalyzed formal homologation of arylboronic acids provides access to these compounds that, in turn, allow the formation of C–C, C–O, and C–N bonds from Pd- and Cu-mediated cross-coupling or oxidative processes. This affords a wide variety of benzylic alcohols, diarylmethanes, benzyl amines, and benzyl ethers. Limitations are disclosed, and the utility is further demonstrated by the generation of analogues of meclizine.
Keywords: boron; catalysis; chemoselectivity; homologation; diversity-oriented synthesis